Achieving biodiversity net gain by addressing governance gaps underpinning ecological compensation policies - Rampling, E; Zu Ermgassen, S; Hawkins, I; Bull, J (Wiley, 2023)
Biodiversity compensation policies have emerged around the world to address the ecological harms of infrastructure expansion, but historically compliance is weak. The Westminster government is introducing a requirement that new infrastructure developments in England demonstrate they achieve a biodiversity net gain (BNG). We sought to determine the magnitude of the effects of governance gaps and regulator capacity constraints on the policy's potential biodiversity impacts. We collated BNG information from all new major developments across six early-adopter councils from 2020 to 2022. We quantified the proportion of the biodiversity outcomes promised under BNG at risk of noncompliance, explored the variation in strategies used to meet developers’ biodiversity liabilities, and quantified the occurrence of simple errors in the biodiversity metric calculations. For large developments and energy infrastructure, biodiversity liabilities frequently met within the projects’ development footprint. For small developments, the purchase of offsets was most common. We estimated that 27% of all biodiversity units fell into governance gaps that exposed them to a high risk of noncompliance because they were associated with better-condition habitats delivered on-site that were unlikely to be monitored or enforced. More robust governance mechanisms (e.g., practical mechanisms for monitoring and enforcement) would help ensure the delivery of this biodiversity on-site. Alternatively, more biodiversity gains could be delivered through off-site biodiversity offsetting. For the latter case, we estimated that the demand for offsets could rise by a factor of 4; this would substantially increase the financial contributions from developers for conservation activities on private land. Twenty-one percent of development applications contained a simple recurring error in their BNG calculations. One-half of these applications were approved by councils, which may indicate under-resourcing in council development assessments. Our findings demonstrate that resourcing and governance shortfalls risk undermining the policy's effectiveness.